2003
DOI: 10.4036/iis.2003.53
|View full text |Cite
|
Sign up to set email alerts
|

Universal Bounds for Genus One Seifert Surfaces for Hyperbolic Knots and Surgeries with Non-Trivial JSJT-Decompositions

Abstract: A universal bound on the number of mutually disjoint non-parallel genus one Seifert surfaces for hyperbolic knots in non-Haken manifolds is given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Then, we have a hyperbolic knot bounding n genus 1 Seifert surfaces which are not mutually parallel. Tsutsumi first showed that the number n is at most 7 ( [41]). After that, Eudave-Muñoz -Ramírez-Losada -Valdez-Sánchez showed that n is at most 6 and provided an example of such embedding of X for n = 5 ([12]).…”
Section: Theorem 313 ([34]) For Equivalence Classesmentioning
confidence: 99%
“…Then, we have a hyperbolic knot bounding n genus 1 Seifert surfaces which are not mutually parallel. Tsutsumi first showed that the number n is at most 7 ( [41]). After that, Eudave-Muñoz -Ramírez-Losada -Valdez-Sánchez showed that n is at most 6 and provided an example of such embedding of X for n = 5 ([12]).…”
Section: Theorem 313 ([34]) For Equivalence Classesmentioning
confidence: 99%
“…Moreover, Kakimizu complexes are simply connected ( [189]) and contractible ( [162]). For a hyperbolic knot of genus 1, the number of mutually disjoint nonparallel genus 1 Seifert surfaces is at most 7 ( [208]). On the other hand, for any natural number n, there exists a hyperbolic knot of genus 1 which bounds mutually disjoint non-parallel Seifert surface of genus 1 and n Seifert surfaces of genus 2 ( [208]).…”
Section: Bridge Decomposing Spheresmentioning
confidence: 99%
“…Then k is a ..1; 0/; .n; m//-curve in @H 0 (Lemma 4.3 of [Tsutsumi 2003]) with jk \ Dj D 2. See Figure 27.…”
Section: Figure 26mentioning
confidence: 99%